Analisis Anggaran Publik dan Non Publik Masa Pandemi (Covid-19) terhadap Penyerapan Tenaga Kerja di Kabupaten Aceh Barat - T. Rifan Handi; Saiful Badli (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This research aims to influence the public budget on labor absorption in West Aceh Regency during the Covid-19 pandemic. This research is quantitative research with a Multiple Linear Regression approach. The subjects of this research are public spending (or realization of direct spending), non-public spending (realization of indirect spending) of the West Aceh Regency government for the 2019-2022 Fiscal Year, and the level of labor absorption and the pandemic period during the first semester 2019-second semester 2022 . Research data is secondary data, sourced from BPS and DPKKD West Aceh Regency. The data collection techniques used were observation and interviews. The results of the t test stated that each variable had a significant effect on the level of labor absorption during the pandemic in West Aceh Regency. The public budget variable partially has a positive and significant effect on the labor absorption variable at the 95 percent confidence level, the non-public budget variable has a significant and negative effect at alpha 0.05. Simultaneous hypothesis testing states that the independent variables public budget and non-public budget together have a positive and significant effect on labor absorption in West Aceh Regency during the pandemic. The results of the correlation test show that the direction of the relationship between the public budget and non-public budget is directly proportional to the level of labor absorption in the very strong category. The coefficient of determination states that the variance in the level of labor absorption can be explained by public budget and non-public budget variables of 92.5 percent and the remaining 7.5 percent is explained by variables outside the model